Beweis: Ableitung der Exponentialfunktion
1. Beweis
1.1. Für die Eulersche Konstante
\begin{align*}
(a^x)' =& \lim_{h \to 0}\left(\frac{a^{x+h} - a^{x}}{x + h - x }\right) \\
=& \lim_{h \to 0}\left(\frac{a^x \cdot \left(a^h - 1\right)}{h}\right) \\
=& a^x \cdot \lim_{h \to 0}\left(\frac{a^h - 1}{h}\right)
\end{align*}
\begin{align*}
e: 1 = \lim_{h \to 0}\left(\frac{e^h - 1}{h}\right)
\end{align*}
1.2. Allgemein
Durch Anwendung der Kettenregel
\begin{align*} (a^x)' =& (e^{\ln(a) \cdot x})' \\ =& (\ln(a) \cdot x)' \cdot e^{\ln(a) \cdot x} \\ =& \ln(a) \cdot a^x \end{align*}